TEKNOLOGI REHABILITASI PADA TANAMAN JAMBU METE - Usman Daras; Bambang Eka Tjahjana (Jurnal Tanaman Industri dan Penyegar, 2011)
Cashew growing in Indonesia is mainly addressed to economic reasons rather than soil and waterconservations of some degraded soils. Main producing areas of the crop are Southeast Sulawesi, South Sulawesi, East Java, Cen tral of Java, East Nusa Tenggara and West Nusa Tenggara provinces covering about 500.000 ha or about 90% of Indonesian cashew. In general, mean yields of the crop is much lower than those of other producing countries like India and Vietnam. Many factors believed affect low in yields of the crop. Increasing in composition of damaged cashew trees to those of the health ones may bring about steadily declining production of Indonesian cashew. In turn, meanyields of the crop achieved are low. Rehabilitation programs of cashew orchard at field levels are therefore needed, mainly to the main growing areas of cashew trees. Field actions that might be implemented for the purposes are pruning, thinning and replanting with high yielding varieties or clones of cashew. To accelerate of recovering of cashew trees, other orchard managements like fertilizing and controlling of some im portant pest and diseases of the crop should be accomplished in better ways.